A tritopic carbanionic N-heterocyclic dicarbene and its homo- and heterometallic coinage metal complexes. Issue 45 (21st May 2018) - Zhang, Fan; Cao, Xiao-Ming; Wang, Jiwei; Jiao, Jiajun; Huang, Yongming; Shi, Min; Braunstein, Pierre; Zhang, Jun
Abstract : Homo (Au3 )- and heterotrinuclear coinage metal complexes (Au2 Ag and Au2 Cu) ligated by the first tritopic dicarbanionic NHC have been prepared by deprotonation of ditopic NHC digold complexes. Abstract : Homo (Au3 )- and heterotrinuclear coinage metal complexes (Au2 Ag and Au2 Cu) ligated by the first tritopic carbanionic N-heterocyclic carbene (NHC) have been prepared by deprotonation of ditopic NHC digold complexes and structurally characterized by single-crystal X-ray diffraction.